Coffee drinking and colorectal cancer and its subsites: A pooled analysis of 8 cohort studies in Japan. Issue 2 (8th March 2018) - Kashino, Ikuko; Akter, Shamima; Mizoue, Tetsuya; Sawada, Norie; Kotemori, Ayaka; Matsuo, Keitaro; Oze, Isao; Ito, Hidemi; Naito, Mariko; Nakayama, Tomio; Kitamura, Yuri; Tamakoshi, Akiko; et al.
Abstract : Coffee is a rich source of bioactive compounds that have potential anticarcinogenic effects. However, it remains unclear whether coffee drinking is associated with colorectal cancer. Also, despite different etiological factors involved in gut physiology, few studies have investigated this association by anatomical site of the lesion. To address these issues, this study examined the association between coffee drinking and colorectal cancer in a pooled analysis from 8 cohort studies conducted in Japan. Among 320, 322 participants followed up for 4, 503, 274 person‐years, 6, 711 incident colorectal cancer cases were identified. Study‐specific hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazards models and then pooled using the random effects model. Coffee drinking was not materially associated with colorectal cancer risk in men or women (pooled HR 0.92, 95% CI 0.82–1.03 in men and pooled HR 0.90, 95% CI 0.76–1.07 in women). Analysis by subsite showed a lower risk of colon cancer among female drinkers of ≥3 cups coffee/day (pooled HR 0.80, 95% CI 0.64–0.99). There was no such association in men. Coffee drinking was not associated with risk of rectal cancer in men or women. Results were virtually the same among never smokers except for an increased risk of rectal cancer associated with frequent coffee consumption. Coffee drinking may be associated with lower risk of colon cancer in Japanese women. Abstract : What's new? Drinking coffee may protect Japanese women from colon cancer, according to new analysis. These authors conducted a pooled analysis of 320, 322 participants from 8 cohort studies out of Japan to investigate the effect of coffee drinking on risk of colorectal cancer. They found no protective or harmful effect on colorectal cancers in men or women. However, when they stratified the data by cancer site, they found a lower risk of colon cancer among women who said they drank 3 or more cups of coffee per day.